Progressing a river health assessment framework to tropical waters - Campos, Camila Aida; Tonin, Alan M.; Sena, Guilherme; Gonçalves Júnior, José Francisco (Frontiers in Water, 2024)
Diverse anthropogenic activities have threatened the valuable tropical biodiversity and freshwater reserves. Despite that, there is little concern in the Brazilian legislation about the ecological integrity of aquatic ecosystems. We proposed a framework based on two joint indices, allowing the creation of a management tool. The first is the Tropical Water Healthy Index (TWHI), a river index that integrates pressures on aquatic ecosystems, their conditions, and societal/governmental response. The second is the Suitability of the Class of Use (SCU), which measures whether rivers’ conditions are in accordance with their classes of use proposed for the legal Brazilian water framework. Our results showed that most sites had good river health conditions, with the worst conditions occurring in areas with high urban occupations followed by agricultural areas. The second index indicated that few streams were poorly or incompatible with their classes of use, suggesting their classifications were based on current conditions but not future intentions. The force of these joint analyses was shown in the Melchior River stretch, which was classified as compatible with SCU, but the TWHI was critical. This is good to show that we simultaneously have a problem with the legislation and to indicate something that needs to be done quickly for managers. Therefore, we built a management model that can assess the real situation of aquatic ecosystems and define efficient management strategies, producing alerts for the decision-maker.